الشيخ مختار بن عطارد البوغوري الجاوي ثم المكي (1862 – 1930) والكتب الصونداوية المطبوعة في مكة والقاهرة أوائل القرن العشرين - Ginanjar Sya'ban (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2021)
This paper examines the history of “Kitab Sunda”, which was written in Sundanese language but with Arabic letter, by Shaikh Mukhtar (1862 – 1930) in Mecca and printed in Cairo and Mecca. While most intellectual works in the Middle East were written in Arabic, there is convincing indication that they were written in non-Arabic language. It is surprising fact that many religious-based works (Islam) were written in Arabic letter, but they used Javanese, Malay and Sundanese. One of important agents of Muslim scholar who purposely used Sundanese language in his work is Shaikh Mukhtar. The writer, born in Bogor (West Java), was a great ulama (Muslim scholar) in Mecca. He was connected with ulama from nusantara and Middle East network in the turn of 19 and 20 century. During the important period, there were some ulama from Sunda who were teaching in Mecca. Some of them wrote books printed in several cities in the Middle East such as Mecca, Cairo and Istanbul. Shaikh Mukhtar is well-known as pioneer of authorship and publicity of Kitab Sunda in Middle East since the early 20th century. Before this period, religious works of ulama nusantara written in nusantara language and printed in the Middle East, only written in Malay language and Javanese. In the Middle East, history of authorship of kitab Sunda was initiated by Shaikh Mukhtar. This achievement is important not only to introduce Sundanese language as the intelectual language in the Middle East through his works, but also inspire his disciple to produce intellectual works in their mother tongue. By means of historical and bibliography of region approach, this study traces the role of Suandanese ulama in Middle East in the early 20th century.